Pedagogues' Attitude towards School Modernization and Their Role in It - Gumuliauskienė, Aušrinė (Acta Paedagogica Vilnensia, 2001)
Lithuanian educational system encounters a complicated task of school, its vision and mission modernization in the context of sociocultural world and European educational concepts. Pedagogues' conception of a modern school is mostly related with material provision, liberalization of training forms, and democratization of relations. Pedagogues’ positive attitude towards school modernization is suppressed by fear of related changes and problems, insufficient initiativity in the searching of modern school, including the following most important ones: permanently deepening conflict between the „generations" of pedagogues, fear to loose job, insufficiently tolerant relations, lack in experience sharing and communication.
Keywords: Educational system; educational change; teacher; school modernization; modern school.